2021
DOI: 10.3389/fmolb.2021.643701
|View full text |Cite
|
Sign up to set email alerts
|

On the Track of the Missing tRNA Genes: A Source of Non-Canonical Functions?

Abstract: Cellular tRNAs appear today as a diverse population of informative macromolecules with conserved general elements ensuring essential common functions and different and distinctive features securing specific interactions and activities. Their differential expression and the variety of post-transcriptional modifications they are subject to, lead to the existence of complex repertoires of tRNA populations adjusted to defined cellular states. Despite the tRNA-coding genes redundancy in prokaryote and eukaryote gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 146 publications
(221 reference statements)
0
21
0
Order By: Relevance
“…This scoring system helps to classify if tRNAs are functional in translation and accounts for tRNA-derived short interspersed repeated elements (SINEs) [ 33 ]. A recent review summarized “missing tRNA genes” across different kingdoms, illustrating that Pro GGG , Leu GAG and Val CAG are absent in 60 eukarya species whereas Asn AUU is absent from 60 eukarya, 100 bacteria, and 50 archaea species [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…This scoring system helps to classify if tRNAs are functional in translation and accounts for tRNA-derived short interspersed repeated elements (SINEs) [ 33 ]. A recent review summarized “missing tRNA genes” across different kingdoms, illustrating that Pro GGG , Leu GAG and Val CAG are absent in 60 eukarya species whereas Asn AUU is absent from 60 eukarya, 100 bacteria, and 50 archaea species [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Like in other bacteria ( 42 ), the tRNA repertoires of the P. aeruginosa PAO1 ( 15 ) and clone C genomes (this work) consist of one, two, or three copies of 37 different isoacceptor genes plus three stop codons (Table S1). The ONT and Illumina platforms detected similar transcript levels of uncharged tRNA isoacceptors in the clone C biological replicates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the different Chargaff’s and Shannon’s scores of the tRNA highlighted in our analysis could take on several aspects, including the principle of purine ejection along the prevailing phylogeny affecting position 34 of the anticodon loop, the wobble position interfering with protein translation, or even tRNA modification depending on Guanosine replacement by Queuosine incorporation or Inosine use. This has probably led to an evolutionary reduction in ambiguous signals or tRNA adaptation phenomena at ribosome sites [ 31 ]. Recent findings have shown that tRNAs may interact with other macromolecules that have no translational functions.…”
Section: Discussionmentioning
confidence: 99%